Corporate governance mechanisms and firm performance of Indonesian family : controlled and non-family controlled companies - , Robin (2019)
This study investigates the relationship between corporate governance mechanisms and performance of Indonesian listed companies. Using panel data approach, the sample consists of 262 companies listed on the Indonesian Stock Exchange for the period between 2010 to 2014. The results show that Indonesian family-controlled companies have better performance than non-family-controlled companies. However, not all attributes of corporate governance mechanisms are significant between family-controlled companies and non-family controlled companies. It is found that larger boards increase the performance of non-family-controlled companies due to their ability to generate more ideas and provide more advice, experience and knowledge, which cannot be found in family directors. Family-controlled companies tend to have small boards; thus, they can make decisions quickly and more easily. Qualifications of directors in larger boards, frequency of board meetings, board expertise and the presence of female directors lead to enhanced performance, both for family-controlled companies and non-family-controlled companies. Boards with higher education and expertise, presence of female directors and more frequent board meetings can provide creative solutions, solve complex problems and improve performance. Directors who hold large managerial ownership tend to concentrate more on personal interests, whilst small board commissioners control the opportunistic behaviour of management and bridge the interests of managers and owners. The findings also suggest that smaller audit committee and higher frequency of audit committee meetings increase the performance of both family- and non-family-controlled companies. On the other hand, the findings show that smaller size of independent audit committee enhance performance for family-controlled companies while larger size for non-family-controlled companies. Thus, regulators need to note the different corporate governance practices between family- and non-family-controlled companies. It is recommended that a pool of independent commissioners with knowledge and experience in enhancing better corporate governance mechanisms be appointed for companies in Indonesia.